1981
DOI: 10.1007/bf01315010
|View full text |Cite
|
Sign up to set email alerts
|

Argentine hemorrhagic fever: Early diagnosis by immunofluorescence

Abstract: A procedure that allows to ascertain a diagnosis of Argentine Hemorrhagic Fever (AHF) as early as 24-48 hours after onset of symptoms is described. An immunofluorescent (IF) test on round cells of urinary sediment was employed. The procedure was assayed on 31 patients with febrile syndrome during epidemic peaks of 1975-1976. It was positive in 19 and negative in 12 cases. The 19 positive cases were confirmed AHF by clinical follow up and serology. From 12 negative cases, 8 belonged to other etiologies and 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Passive immunization, for example by application of convalescent plasma, is an approach to bridge the critical phase between virus replication and the onset of the patient 0 s own adaptive humoral immune response. Convalescent plasma has been used successfully for treatment of diseases such as severe viral acute respiratory infections and Argentine haemorrhagic fever [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunization, for example by application of convalescent plasma, is an approach to bridge the critical phase between virus replication and the onset of the patient 0 s own adaptive humoral immune response. Convalescent plasma has been used successfully for treatment of diseases such as severe viral acute respiratory infections and Argentine haemorrhagic fever [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are documented cases of other viral hemorrhagic fever viruses being detected in saliva or in urine by PCR methods, and it has been reported that these samples could be used for diagnostic purposes. [8][9][10] Additionally, it has been suggested that specific IgM antibodies in saliva are useful markers for the detection of dengue infection. 11 In this brief work, we have only studied the detection of viral genomes of CCHF in saliva and urine and made comparisons to the viral RNA load in blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on this, stretching over approximately three decades, showed a substantial difference in total mortality among patients diagnosed with traditional or CP care. 46 Likewise, patients diagnosed with Lassa fever, another type of viral hemorrhagic fever, apparently showed reassuring results after receiving CP. 47 Despite procedural limitations and insufficient statistics, reference from above cited studies corresponds to the use of CP for various infections known.…”
Section: Advancements In Convalescent Blood or Plasma Therapy Since 1890mentioning
confidence: 99%